Lactic Acid Bacteria in Finfish—An Update - Ringø, Einar; Hoseinifar, Seyed Hossein; Ghosh, Koushik; Doan, Hien Van; Beck, Bo Ram; Song, Seong Kyu (Frontiers in Microbiology, 2018)
Fish intestinal mucosal surfaces comprise of a complex and dynamic community of microorganisms, which play important roles within the gastrointestinal (GI) tract. Of the bacteria colonising the GI tract, lactic acid bacteria (LAB), are generally considered as favourable bacteria due to their abilities to stimulating host GI development, digestive function, maintaining mucosal tolerance, stimulating immune response and provide protection towards bacterial pathogens. In early finfish studies culture-dependent methods were used to enumerate bacterial population levels within the GI tract; members of Lactobacillus, Lactococcus, Leuconostoc, Enterococcus, Streptococcus and Carnobacterium genera were isolated. However, due to limitations by using culture media, techniques such as denaturing gradient gel electrophoresis (DGGE), temporal temperature gradient electrophoresis (TTGE), 16S rRNA clone libraries, and MiSeq sequencing of 16S rRNA genes have been used during the last decade. These investigations have revealed the presence of Lactobacillus, Lactococcus, Leuconostoc, Enterococcus, Streptococcus, Carnobacterium, Weissella and Pediococcus as indigenous species. In the GI tract of warm water fish species, members of the genera Lactobacillus, Lactococcus, Leuconostoc, Enterococcus, Weissella and Pediococcus have commonly been identified, however, Carnobacterium are rarely identified. Numerous strains of LAB isolated from finfish are capable of producing antibacterial substances against different potential fish pathogenic bacteria as well as human pathogens. In addition, many LAB have the ability to inhibit growth of closely related bacteria including strains of carnobacteria, lactobacilli, lactococci, leuconostoc and pediococci. LAB are revealed be the most promising bacterial genera as probiotic in aquaculture. During the decade increasing number of research attempts are performed on evaluation of probiotic properties of different genus and species of LAB. Except limited contradictory reports, most of administered strains showed beneficial effects on growth performance, reproductive performance, immune responses and disease resistance of finfish. This eventually led to industrial scale up and introduction LAB-based commercial probiotics. Pathogenic LAB such as members of the genera Streptococcus, Enterococcus, Lactobacillus, Carnobacterium and Lactococcus have been detected from ascites, kidney, liver, heart and spleen of several finfish species. These pathogenic bacteria will be addressed in present review which includes their impacts on finfish aquaculture, possible routes for treatment.